2012
DOI: 10.1155/2012/542976
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic-Ischemic Injury in the Developing Brain: The Role of Reactive Oxygen Species Originating in Mitochondria

Abstract: Mitochondrial dysfunction is the most fundamental mechanism of cell damage in cerebral hypoxia-ischemia and reperfusion. Mitochondrial respiratory chain (MRC) is increasingly recognized as a source for reactive oxygen species (ROS) in the postischemic tissue. Potentially, ROS originating in MRC can contribute to the reperfusion-driven oxidative stress, promoting mitochondrial membrane permeabilization. The loss of mitochondrial membranes integrity during reperfusion is considered as the major mechanism of seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 87 publications
1
72
0
1
Order By: Relevance
“…One of the better-characterized ways in which liver cells adapt to starvation is through phosphorylation-mediated inhibition of pyruvate dehydrogenase (Huang et al, 2003), which reduces mitochondrial utilization of pyruvate and has been proposed to increase ROS production (Ten and Starkov, 2012). We recently reported that electrons derived from NADH and FADH 2 follow separate routes along the mETC, and that this is important for metabolic adaptation to starvation, with an increase in the rate of FADH 2 oxidization occurring at the expense of the NADH route (Lapuente-Brun et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…One of the better-characterized ways in which liver cells adapt to starvation is through phosphorylation-mediated inhibition of pyruvate dehydrogenase (Huang et al, 2003), which reduces mitochondrial utilization of pyruvate and has been proposed to increase ROS production (Ten and Starkov, 2012). We recently reported that electrons derived from NADH and FADH 2 follow separate routes along the mETC, and that this is important for metabolic adaptation to starvation, with an increase in the rate of FADH 2 oxidization occurring at the expense of the NADH route (Lapuente-Brun et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, RET also provided the greatest rate in H 2 O 2 release equivalent to around 3.5% of total oxygen consumption, which is very close to what observed for the mitochondria from adult rat brain 26 . Therefore, in postischemic tissue, RET is active and may render injury to the tissue found in several models of tissue ischemia 18,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is the most fundamental mechanism of cell damage in cerebral ischemia-reperfusion injury as it has critical roles in the apoptotic pathway in ischemic injury (34). Ischemia-reperfusion impairs mitochondrial function and leads to an increase of mitochondrial membrane permeability, resulting in release of cytochrome c, caspase-3 activation and apoptotic cell death (34).…”
Section: Discussionmentioning
confidence: 99%